The association of statin subgroups with lower urinary tract symptoms following a prostate biopsy - Goldberg, Hanan; Mohsin, Faizan K.; Chandrasekar, Thenappan; Wallis, Christopher J.D.; Klaassen, Zachary; Ahmad, Ardalan E.; Saskin, Refik; Kenk, Miran; Saarela, Olli; Kulkarni, Girish S.; et al. (Canadian Urological Association Journal, 2021)
Introduction: This was a secondary analysis aiming to assess whether hydrophilic or hydrophobic statins have a differential effect on urinary retention (UR) and lower urinary tract symptoms (LUTS) in men following a prostate biopsy (PBx), who were at risk for prostate cancer development. Methods: This was a population-based cohort study with data incorporated from the Institute for Clinical and Evaluative Sciences database to identify all Ontarian men aged 66 and above with a history of a single negative PBx between 1994 and 2016, with no drug prescription history of any of several putative chemopreventative medications (statins, proton pump inhibitors, five alpha-reductase inhibitors, and alpha-blockers). Multivariable Cox regression models with time-dependent covariates were used to assess the association of hydrophilic and hydrophobic statins with UR and LUTS within 30 days of a PBx. All models were adjusted for other known putative chemopreventive medications, age, rurality, pharmacologically treated diabetes, comorbidity score, and study inclusion year. Results: Overall, 21 512 men were included, with a median followup time of 9.4 years (interquartile range [IQR] 5.4–13.4 years). Hydrophobic and hydrophilic statins were initiated by 30.7% and 19.6% of men, respectively, after the first negative PBx. UR and LUTS were experienced by 2.2% and 10% of men, respectively. Cox models demonstrated hydrophilic statins were associated with a lower risk of UR (hazard ratio [HR] 0.56, 95% confidence interval [CI] 0.38–0.83, p=0.0038) and LUTS (HR 0.86, 95% CI 0.76–0.98, p=0.022), while no such association was shown for hydrophobic statins. Conclusions: Initiation of hydrophilic statins in men older than 66 appears to be inversely associated with the risk of UR and LUTS within 30 days of a PBx.